Review of Some Procedural Witness Protective Measures at the International Criminal Tribunal for the Former Yugoslavia - Beqiri, Romina (European Scientific Journal, ESJ, 2017)
Given the spread terror and the abuses perpetrated in the Balkan region, many victims and witnesses of atrocities were deterred from testifying. The International Criminal Tribunal for the former Yugoslavia (ICTY or Tribunal) facilitated the appearance of witnesses and protected them in case of intimidation including by taking measures against those who would violate the confidentiality of the proceedings. This article aims to introduce some of the witness protective measures before the Tribunal, and particularly threats and risks they have faced in the context of the cases dealt with by the Tribunal. It reflects also upon groundbreaking measures of protection decided by the Tribunal and the challenges it has faced over the last two decades. It finally discusses the impact of such challenges on the right to a fair trial and how they were addressed.